Architecture and prototype of the CMS Global Level-1 Trigger for Phase-2. (1st January 2023) - Bortolato, G.; Deldicque, C.; Gigi, D.; Huber, B.; Leutgeb, E.; Lobanov, A.; Rabady, D.; Racz, A.; Sakulin, H.; ,
Abstract: We present the architecture and current state of prototype firmware of the CMS Level-1 Global Trigger, the final stage of the new Level-1 trigger for Phase-2 of the LHC. Based on high-precision inputs from the muon, calorimeter, track and particle flow triggers, the Global Trigger evaluates O(1000) cut-based and neural-net-based algorithms in a system of up to thirteen Xilinx Ultrascale+ based ATCA processing boards interconnected by 25 Gb/s optical links. In order to optimize the usage of resources, the main algorithms, including the DSP-based calculation of invariant masses, are implemented at 480 MHz.